2015
DOI: 10.1016/j.nutres.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Prosteatotic genes are associated with unsaturated fat suppression of saturated fat-induced hepatic steatosis in C57BL/6 mice

Abstract: Both high sugar and fat diets can induce prosteatotic genes, leading to obesity and obesity-associated diseases, including hepatic steatosis. Unsaturated fat/fatty acid (USFA) reduces high sugar-induced hepatic steatosis by inhibiting the induced prosteatotic genes. In contrast, it is still unclear how USFA ameliorates saturated fat/fatty acid (SFA)-induced hepatic steatosis. As sugar and fat have different transport and metabolic pathways, we hypothesized that USFA suppressed SFA-induced hepatic steatosis via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 54 publications
(62 reference statements)
1
18
0
Order By: Relevance
“…2A). Although this is consistent with previous reports (Kim et al, 2004;Kudo et al, 2009;Geng et al, 2015), others have reported decreased hepatic Cyp3a11 expression or activity upon HFD feeding in mice (Yoshinari et al, 2006;Ghose et al, 2011;Wahlang et al, 2014). Differences in diet composition and housing condition may have contributed to the discrepancy.…”
Section: Resultssupporting
confidence: 92%
“…2A). Although this is consistent with previous reports (Kim et al, 2004;Kudo et al, 2009;Geng et al, 2015), others have reported decreased hepatic Cyp3a11 expression or activity upon HFD feeding in mice (Yoshinari et al, 2006;Ghose et al, 2011;Wahlang et al, 2014). Differences in diet composition and housing condition may have contributed to the discrepancy.…”
Section: Resultssupporting
confidence: 92%
“…A recent study from our laboratory demonstrated that dietary fat composition (i.e., saturated vs. unsaturated) had a profound effect on deleterious liver outcomes, including ER stress, liver weight, and hepatic steatosis, which are components of NAFLD ( 22,(26)(27)(28)(29)(30). Moreover, other studies in our laboratory and others indicated that palmitate (C16:0), but not oleate (C18:1), increased expression of SphK1 in skeletal muscle, and that the enzyme was required for expression of proinfl ammatory genes in primary skeletal muscle cells and also in skeletal muscle in mice on a highfat diet ( 7,13 ).…”
Section: Resultsmentioning
confidence: 99%
“…The protocol for immunoblot analysis was also previously described60. The following antibodies were used in this study: Complement C5 (Cat.…”
Section: Methodsmentioning
confidence: 99%